Economic Growth and Its Determinants in Less-Developed Regions: A Panel Quantile Approach - Malik, Fania; Panjawa, Jihad Lukis; Islami, Fitrah Sari; Sugiharti, Rr. Retno (Universitas Airlangga, 2025)
Economic growth is an important phenomenon because it is closely related to the ultimate goal of development, namely community welfare. However, not all regions in Indonesia have experienced an increase in economic growth. Less-developed regions are among those with low economic growth. This study aims to analyze the determinant of economic growth in 40 less-developed regions of Indonesia during 2015-2022 using a quantile panel regression analysis tool. The results show that the fixed capital formation, population, and human development have a significant positive effect on economic growth at low, medium, and high levels of economic growth. The internet usage variable has a significant positive effect on low and medium economic growth levels but has no effect on high economic growth levels. The access to clean water variable has a significant positive effect on low economic growth levels but has a significant negative effect on medium economic growth levels. Meanwhile, at high economic growth levels, access to clean water has no effect. The government is more committed to accelerating development and the community must actively cooperate in regional development to increase regional economic growth.